Kinetics of mass transfer during osmotic dehydration of auyama (Caribbean pumpkin) in ternary solutions (2019)
The aim of this study was to address the modeling of aspects such as weight reduction (WR), solid gain (SG) and weight-loss (WL) in Caribbean pumpkin samples osmotically dehydrated in ternary solutions. For this purpose, osmotic dehydration was carried out using two ternary solutions: stevia-salt-water (S1) and glucose-salt-water (S2) at different concentrations (20%, 30% and 40% w/w), and processing times of 40 min, 80 min, 120 min, and 160 min. Also, the diffusion coefficient was determined and the analysis of variance with orthogonal polynomials was performed to find the best treatment for dehydration of auyama samples (p≤0.05). The results suggest that the solution constituted by stevia-salt-water, allows greater reduction of weight and gain of solids when a concentration of 40% is used at a time of 78.12min until reaching a humidity percentage of 60.06%. Similarly, the values of the diffusion coefficient for this solution ratify that the increase in concentration generates less resistance to mass transfer